The Advancing Role of Neuromodulation for the Management of Chronic Treatment-Refractory Pain. Issue 3 (21st February 2017) - Shamji, Mohammed F.; De Vos, Cecile; Sharan, Ashwini
Abstract: Neuropathic pain is a common cause of disability and health care utilization. While judicious pharmacotherapy and management of comorbid psychological distress can provide for improved quality of life, some patients with treatment-refractory disease require more invasive therapies. Spinal cord stimulation can provide for improvement in pain and decrease in medication utilization, with level 1 evidence supporting its use across various pain etiologies including persistent postoperative neuropathic pain, complex regional pain syndrome, chronic inoperable limb ischemia, treatment refractory angina, and painful diabetic neuropathy. These procedures can be done with acceptably low morbidity and provide a cost-effective solution for those patients in whom medical therapies have failed. Technological innovation in lead design, implantable pulse generator capability, and stimulation algorithms and parameters may further enhance the success of this therapy. Neuromodulation of distal targets such as dorsal root ganglion may permit greater anatomic specificity of the therapy, whereas subthreshold stimulation with high-frequency or burst energy delivery may eliminate noxious and off-target paresthesiae. Such new technologies should be subject to rigorous evaluation as their mechanisms of action and long-term outcomes remain hitherto undefined.